Atitudini politice ale studenților români - Keil, Thomas (Calitatea Vieții, 1992)
Using both latent and observed variables, this paper is an attempt to describe the political attitudes of Romanian students in terms of path analysis. Data and specific path statistics are handled using LISREL. The model focuses upon a sample of 624 students questioned in 1991.